Big food and the World Health Organization: a qualitative study of industry attempts to influence global-level non-communicable disease policy. Issue 6 (11th June 2021) - Lauber, Kathrin; Rutter, Harry; Gilmore, Anna B
Abstract : Introduction: There is an urgent need for effective action to address the over 10 million annual deaths attributable to unhealthy diets. Food industry interference with policies aimed at reducing non-communicable diseases (NCDs) is widely documented at the national level but remains under-researched at the global level. Thus, this study explores how ultra-processed food industry actors have attempted to influence NCD policy at WHO. Methods: A combination of inductive and deductive thematic coding of internal industry documents, academic literature and interviews with key informants from international organisations and global civil society was used to identify action-based strategies ultra-processed food industry actors employ to influence global-level policy. Results: Ultra-processed food industry actors have attempted to influence WHO and its policies through three main action-based strategies: coalition management, involvement in policy formulation, and information management. Coalition management includes the creation and use of overt alliances between corporations—business associations—and more covert science-focused and policy-focused intermediaries, the hiring of former WHO staff and attempted co-option of civil society organisations. Industry involvement in policy formulation is operationalised largely through the lobbying of Member States to support industry positions, and business associations gaining access to WHO through formal consultations and hearings. Information management involves funding and disseminating research favourable to commercial interests, and challenging unfavourable evidence. Conclusion: We provide novel insights into how ultra-processed food industry actors shape global-level NCD policy and identify a clear need to guard against commercial interference to advance NCD policy. In their approach, the political behaviour of multinational food corporations bears similarities to that of the tobacco industry. Increased awareness of, and safeguarding against, commercial interference at the national as well as the global level have the potential to strengthen the crucial work of WHO.